2019
DOI: 10.1007/s13595-019-0898-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased tolerance to Phytophthora cinnamomi in offspring of ink-diseased chestnut (Castanea sativa Miller) trees

Abstract: & Key message Increased tolerance to Phytophthora cinnamomi was observed in small-sized offspring of ink-diseased chestnut trees, suggesting that a virulent pathogen can trigger a defence response of trees in the subsequent generation. Increased tolerance to water stress was not observed in offspring of chestnut trees. & Context In sweet chestnut (Castanea sativa Miller), P. cinnamomi Rands is responsible for the widespread and destructive ink disease. & Aims We investigated if the susceptibility of C. sativa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…This riparian forest has a Mediterranean climate, with mean air temperature of 14.9°C and mean annual precipitation of 1005 mm. Isolations of P. cinnamomi from the rhizosphere of symptomatic trees suggested that they were infected, whereas no P. cinnamomi was isolated from the rhizosphere of healthy trees (Camisón et al., 2019). Healthy and declining alders were located along the river Jerte, Plasencia, Spain (40°01′51.2″N 6°04′46.0″W; 329 m a.s.l.…”
Section: Methodsmentioning
confidence: 99%
“…This riparian forest has a Mediterranean climate, with mean air temperature of 14.9°C and mean annual precipitation of 1005 mm. Isolations of P. cinnamomi from the rhizosphere of symptomatic trees suggested that they were infected, whereas no P. cinnamomi was isolated from the rhizosphere of healthy trees (Camisón et al., 2019). Healthy and declining alders were located along the river Jerte, Plasencia, Spain (40°01′51.2″N 6°04′46.0″W; 329 m a.s.l.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of the maternal environment has also been shown to play an important role in the tolerance level of the offspring to various pathogens. Individuals from mother plants exposed to pathogens appear to be more tolerant to these same pathogens, and authors hypothesized that epigenetic mechanisms may be involved in this priming phenomenon [149,150]. Recently, Lamelas et al (2020) [151] proposed the importance of epigenetic mechanisms for P. radiata heat stress tolerance and priming by evaluating the nuclear proteome and tissue DNA methylation dynamics of seedlings submitted to 45 • C for 10 days, allowed to recover, and submitted to another stress cycle.…”
Section: Figurementioning
confidence: 99%
“…Environmental maternal effects on the tolerance of Pinus pinaster to biotic stress have been reported 32 . In addition, a recent work 35 , demonstrated that chestnut (Castanea sativa) seedlings of ink-diseased mother trees showed increased tolerance to P. cinnamomi; interestingly, this tolerance was not mediated by seed size, but probably as a consequence of seed priming during fruit development. These inheritable variations could open doors for obtaining resistant or tolerant oak genotypes, which would be included in a recovery program in damaged areas, avoiding oak woodlands and dehesa dieback.…”
mentioning
confidence: 98%